The efficacy of combined Intense pulsed light plus high-intensity focussed ultrasound with two different powers in the treatment of atrophic and Icepick acne scars - Fatima Ahmed Salem; Mustafa Salih Ali Al Musawi; Wisam Majeed Kattoof (Journal of the Pakistan Medical Association, 2024)
Objective: To determine the clinical efficacy and suitable power of high-intensity focussed ultrasound combined with intense pulsed light to treat acne scarring. Methods: The prospective study was conducted at the College of Medicine, Mustansiriyah University, Baghdad, Iraq, from September 2020 to March 2021, and comprised patients of either gender with atrophic or icepick scars. They were divided into atrophic scar group A and icepick scar group B. Both groups were first treated with intense pulsed light and then with high-intensity focussed ultrasound using 30J/cm2 and 40J/cm2 power. There were overall 4 sessions with an interval of 4 weeks. The outcome was assessed using the Patient and Observer Scar Assessment Scale. Data was analysed using SPSS 25. Results: Of the 22 patients with a mean age of 20.86±3.22 years, there were 11patients in group A; 7(70%) females and 4(30%) males with a mean age of 20.5±2.06 years. There were 11patients in group B; 7(70%) males and 4(30%) females with a mean age of 21.27±4.19 years. There was a significant difference between baseline and post-intervention scores for both groups (p<0.05), and power 30J/cm2 was significantly better compared to 40J/cm2 (p<0.05). Conclusion: The developing technique using high-intensity focussed ultrasound and intense pulsed light was found to be effective in treating scars with 30J/cm2 power. Key Words: Cicatrix, Tissue diseases, Atrophy, Acne vulgaris, Icepick.